Study of the impact of drought on the runoff system and the dam on Oued Za using romote sensing techniques (Eastern Morocco) - Karboub Abdelaziz; Ghzal Mohammed; Sbai Abdelkader; Mouadili Omar (E3S Web of Conferences)
The irregularity of precipitation that most Moroccan territories receive is mainly due to the association of precipitation with the atmospheric system in general. This phenomenon has an obvious impact, particularly in semi-arid areas, which suffer from scarcity of water resources and low precipitation rates. In turn, the Oued El Hay basin (northern margins of the highlands) is characterized by aridity resulting from its difficult climatic conditions, since climatic elements have an important and decisive role in the periodic and more severe occurrence of droughts, due to their seasonal variations throughout the year. This is directly reflected in the general water supply, whether surface runoff, which remains low in the region, or groundwater, which is directly affected by prevailing climatic conditions. The fluctuation and lack of precipitation is reflected in the water inputs that feed the groundwater, given the excessive exploitation to which the water is exposed to meet the growing needs of the region. Given the relationship between surface runoff and the volume of water supplies mobilized, the frequency of droughts has a significant impact on the volume and supply of water mobilized by dams. At the basin level, a significant drop in the volume of inflows was recorded at the dam on Oued Za. The maximum recorded in 2004/2005 did not exceed 46 million m³. This article aims to highlight the impact of drought on the surface runoff system of Oued El Hay, to study the evolution of the volume of water from the dam on Oued Za based on data recorded between 1978/79 and 2020/21, and to monitor the volume of water mobilized using remote sensing techniques.